Conjuring Crisis : Racism and Civil Rights in a Southern Military City. - Baca, George (Rutgers University Press, 2010)
How have civil rights transformed racial politics in America? Connecting economic and social reforms to racial and class inequality, Conjuring Crisis counters the myth of steady race progress by analyzing how the federal government and local politicians have sometimes "reformed" politics in ways that have amplified racism in the post civil-rights era. In the 1990s at Fort Bragg and Fayetteville, North Carolina, the city's dominant political coalition of white civic and business leaders had lost control of the city council. Amid accusations of racism in the police department, two white council m.